2013
DOI: 10.1371/journal.pbio.1001715
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs Promote Transcriptional Poising of Inducible Genes

Abstract: The GAL cluster-associated long non-coding RNAs (lncRNAs) promote rapid induction of GAL genes in budding yeast, thereby promoting a faster switch in transcriptional programs when needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 80 publications
(185 reference statements)
5
57
0
Order By: Relevance
“…The FLO11 gene encodes a cell wall protein regulating adhesion between cells, and its expression is controlled by a pair of lncRNAs from the upstream region (24). lncRNAs have been proposed to regulate gene induction at the PHO5 (22) and GAL loci (21,52). A proposed mechanism involving transcriptional displacement of the Cyc8 repressor (20) is mechanistically similar to our model at HO.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The FLO11 gene encodes a cell wall protein regulating adhesion between cells, and its expression is controlled by a pair of lncRNAs from the upstream region (24). lncRNAs have been proposed to regulate gene induction at the PHO5 (22) and GAL loci (21,52). A proposed mechanism involving transcriptional displacement of the Cyc8 repressor (20) is mechanistically similar to our model at HO.…”
Section: Discussionsupporting
confidence: 66%
“…Long noncoding RNAs (lncRNAs) can regulate transcription (14)(15)(16)(17), and in budding yeast lncRNAs have been implicated in promoter regulation (18)(19)(20)(21)(22)(23)(24). Here we decipher the mechanism by which mating pheromone blocks expression of the HO endonuclease during the subsequent cell cycle.…”
Section: Significancementioning
confidence: 99%
“…In addition to transcriptional repression, our group discovered that the GAL10 and GAL10s lncRNAs also function in transcriptional activation from transcriptionally repressive (Cglucose) to activating (¡galactose) conditions. 52 During this switch, the GAL lncRNAs enhance induction of the GAL protein coding genes from a repressed state by interfering with binding of the Tup1/Cyc8-corepressor complex. This occurs, presumably, by physical occlusion of the complex and results in derepression of the glucose-repressed GAL genes and allows for faster transcriptional activation in the presence of galactose (Fig.…”
mentioning
confidence: 99%
“…Interestingly, we found that cells lacking DBP2 display a much more rapid lncRNA-dependent transcriptional induction of the GAL genes, as well as reduced association of the Cyc8 corepressor. 52 This suggested that Dbp2 and/or its role in RNP assembly, antagonizes the transcriptionally activating role of the GAL lncRNAs and that dbp2D cells could be used as a tool to decipher the mechanism of transcriptional induction by these noncoding molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation